First Reported Case of Proliferative Retinopathy in Hemoglobin SE Disease. (21st August 2014) - Baciu, Paul; Yang, Christopher; Fantin, Aldo; Darnley-Fisch, Deborah; Desai, Uday
Abstract : We report the first case of proliferative sickle cell retinopathy in a patient with hemoglobin SE (Hb SE) disease. Only a few dozen cases of Hb SE disease have been reported previously, and none had evidence of proliferative retinopathy. A 56-year-old African American man presented to our clinic for routine examination and was found to have sea-fan peripheral neovascularization bilaterally without maculopathy. Hemoglobin analysis revealed Hb SE heterozygosity. Sector laser photocoagulation to areas of nonperfusion in both eyes resulted in regression of the peripheral neovascularization over a period of 6 months. Although Hb SE disease is rare, the incidence of Hb SE disease is postulated to rise in the future. Awareness of its potential ocular complications is needed to appropriately refer these patients for screening.